Territorialisation dynamics for Italian farms adhering to Alternative Food Networks - Marino, Davide; Mastronardi, Luigi; Giannelli, Agostino; Giaccio, Vincenzo; Mazzocchi, Giampiero (Bulletin of Geography. Socio-economic Series, 2018)
The demographic processes of the last decades have led to variations in urban and peri-urban territorial configurations, questioning the patterns of traditional productive localisation. They have begun to outline new perspectives related to proximity to trading and commerce sites as well as to the services offered by the city. Business strategies, such as multifunctionality and diversification, have begun to consider these new possibilities that, at a larger scale, have triggered the process of territorialisation. The study analyses the influence of proximity to the city on the strategies of farms diversifying income through short food chains, with the aim of identifying the prevailing behaviours adopted in three different concentric areas at the urban centre of gravity: peri-urban, belt and rural. The study involves a dataset constituted by 217 farms, where each farm has been associated with a set of explanatory variables that outline some structural, social and economic characteristics. The sample has been segmented through a hierarchical cluster analysis, which allowed us to identify 5 groups of farms, after having reduced the number of variables through PCA (Principal Component Analysis). The results show that short food chains and, more generally, AFNs, are based on strategies alternative to those of traditional chains, and which involve a different economic dimension of the same chains and the construction of a different place-based agro-food system, also envisaging a re-localisation of space near the final market.